PENGUJIAN TERHADAP TINGKAT "PRO POOR BUDGETING" PADA KABUPATEN DAN KOTA DI JAWA - Esa Pramesti (AKT 11 UMY 514, 2011)

(untitled)
The purpose of this research is to examine the influence of the indirect personnel expenditure, direct personnel expenditure, goods and services expenditure, capital expenditure due to the local independence and poverty. The research is also to observe the local independence by using the intervening variable from the influence of indirect personnel expenditure, direct personnel expenditure, goods and services expenditure, capital expenditure due to poverty. The research means to examine if the b